Influencer Communication Strategies in Building Personal Branding on Social Media - Ld. Muh. Zaitullah; Muhammad Hidayatullah (Jogjakarta Communication Conference (JCC), 2026)
The rapid growth of social media has transformed the way individuals communicate, construct identity, and build influence in digital environments. Within this context, influencers play an important role in shaping audience perceptions, promoting products, and disseminating information through online platforms. This study aims to analyze the communication strategies used by local influencers in Baubau City to build personal branding on social media and to examine differences between influencers who consciously develop personal branding and those whose branding emerges organically. This research employed a qualitative descriptive approach to explore influencer communication practices within their natural digital environments. Data were collected through observation, in depth interviews, and documentation involving three local influencers who actively produce content on social media. The data were analyzed using the Miles and Huberman -qualitative analysis model, which includes data reduction, data presentation, and conclusion drawing. The findings reveal that influencers produce content for multiple purposes, including gaining recognition, supporting local businesses, and generating economic benefits through digital collaborations. Storytelling, simple language, and audienceoriented communication styles were identified as the main strategies used to deliver messages effectively. The study also found differences in personal branding awareness among influencers. Some influencers deliberately design their branding through consistent content themes, slogans, and distinctive communication styles, while others develop their online identities gradually through ongoing interaction with audiences. Authenticity and ethical communication practices were also found to be essential for building audience trust and sustaining credibility. Overall, the study highlights the importance of strategic communication, authenticity, and content consistency in developing personal branding among local influencers. The findings contribute to the understanding of influencer communication within regional digital ecosystems and provide practical insights for emerging influencers seeking to build sustainable online identities.